2003
DOI: 10.1242/jcs.00250
|View full text |Cite
|
Sign up to set email alerts
|

A plant cyclin B2 is degraded early in mitosis and its ectopic expression shortens G2-phase and alleviates the DNA-damage checkpoint

Abstract: Mitotic progression is timely regulated by the accumulation and degradation of A- and B-type cyclins. In plants, there are three classes of A-, and two classes of B-type cyclins, but their specific roles are not known. We have generated transgenic tobacco plants in which the ectopic expression of a plant cyclin B2 gene is under the control of a tetracycline-inducible promoter. We show that the induction of cyclin B2 expression in cultured cells during G2 phase accelerates the entry into mitosis and allows cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 71 publications
3
52
0
2
Order By: Relevance
“…Similarly, in a cell suspension culture of alfalfa (Medicago sativa), PSTAIREholding CDKs have been found to undergo Tyr phosphorylation (Mé szá ros et al, 2000). In mammalian cells, the drug caffeine cancels the DNA replication checkpoint through inhibition of the ATM kinase (Schlegel and Pardee, 1986;Andreassen and Margolis, 1992;Blasina et al, 1999), but in plants, it overrides the replication checkpoint only in the presence of the mitotic cyclin CYCB2 (Weingartner et al, 2003). Therefore, we postulate that among many other partnerships, CDKA;1 in complex with the B2-type cyclin might be the major target for inhibition by the activated checkpoint control pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a cell suspension culture of alfalfa (Medicago sativa), PSTAIREholding CDKs have been found to undergo Tyr phosphorylation (Mé szá ros et al, 2000). In mammalian cells, the drug caffeine cancels the DNA replication checkpoint through inhibition of the ATM kinase (Schlegel and Pardee, 1986;Andreassen and Margolis, 1992;Blasina et al, 1999), but in plants, it overrides the replication checkpoint only in the presence of the mitotic cyclin CYCB2 (Weingartner et al, 2003). Therefore, we postulate that among many other partnerships, CDKA;1 in complex with the B2-type cyclin might be the major target for inhibition by the activated checkpoint control pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In our simulations, activation of mitotic cyclin transcription by MPF (M phase promoting factor, called MPF* in our model) could establish a long G2 phase in the absence of a CDK-CDC25-WEE1 loop ( Figure 8C). Interestingly, ectopic expression of a tobacco CYCB2 in BY2 cells was found to push cells into mitosis, indicating that transcriptional regulation of mitotic cyclins is indeed sufficient to modulate the length of G2 phases (Weingartner et al, 2003).…”
Section: Control Of Mitotic Entry In Plantsmentioning
confidence: 99%
“…CDK-A or -B play a pivotal role in the G 1 /S and G 2 ∕M transition points (Harting and Beck, 2006). In plants mitotic progression is timely regulated by the accumulation and degradation of the mitotic cyclins A-and B-type (Weingartner et al, 2003). The inhibition in mitotic division obtained in this work may be explained according the work of Zhang and Turner, 2008 who showed that high concentrations of jasmonic acid reduced cell number by inhibiting cell division as a consequence of a G 2 arrest due to repression of cycB1 and cycB2 gene expression.…”
Section: Resultsmentioning
confidence: 99%